PELATIHAN IMPLEMENTASI E-COMMERCE UNTUK MENANGKAP PELUANG USAHA BAGI GENERASI MUDA DI KELURAHAN KUTA - Purnawan, I.K.A. (Buletin Udayana Mengabdi, 2016)
Purpose devotion wants to provide knowledge and skills to the younger generation by utilizing e-commerce technology. The material provided on the application of e-commerce and how to use e-commerce so as to provide benefits and business opportunities. This dedication was held in Kuta Village to target the younger generation. This devotion cooperation with the Lembaga Pemberdayaan Masyarakat Kelurahan Kuta to maximize the implementation of the training. The method used is to provide training materials through the presentation, along with the implementation of e-commerce training. The achievement of this devotion is the implementation of service activities as expected which enthusiastically followed until the end of the event. Participants gain knowledge and skills about the implementation of e-commerce to capture business opportunities.
Keywords: training; e-commerce; technology; business; kelurahan kuta; youth